A guideline for the clinical management of basal cell naevus syndrome (Gorlin–Goltz syndrome). (1st February 2022) - Verkouteren, B.J.A.; Cosgun, B.; Reinders, M.G.H.C.; Kessler, P.A.W.K.; Vermeulen, R.J.; Klaassens, M.; Lambrechts, S.; van Rheenen, J.R.; van Geel, M.; Vreeburg, M.; Mosterd, K.
Abstract: Linked Comment:  E. Epstein. Br J Dermatol 2022; 186:203 . Plain language summary available online